2021
DOI: 10.1017/s0714980821000106
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Volunteers in Enhancing Resident Quality of Life in Long-Term Care: Analyzing Policies that May Enable or Limit this Role

Abstract: Research has shown that long-term care (LTC) volunteers play important roles in enhancing the quality of life (QoL) of older LTC residents, often through providing unique forms of relational care. Guided by Kane’s QoL domains, we used a modified objective hermeneutics method to analyze how unique volunteer roles are represented and supported in provincial policies in Alberta, British Columbia, Ontario, and Nova Scotia. We found that policies define volunteer roles narrowly, which may limit residents’ QoL. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Social connectedness is associated with better well-being and contributes to better QoL for LTC residents (Bethell et al, 2021; Hande, Taylor, & Keefe, 2021). Studies have shown that self-isolation restrictions during the pandemic have increased anxiety and loneliness in older adults (Hwang, Rabheru, Peisah, Reichman, & Ikeda, 2020; Sepúlveda-Loyola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Social connectedness is associated with better well-being and contributes to better QoL for LTC residents (Bethell et al, 2021; Hande, Taylor, & Keefe, 2021). Studies have shown that self-isolation restrictions during the pandemic have increased anxiety and loneliness in older adults (Hwang, Rabheru, Peisah, Reichman, & Ikeda, 2020; Sepúlveda-Loyola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, SALTY organized three in-person meetings where advisors’ travel, food, and accommodation was covered by research funds. SALTY’s essential voice advisors are acknowledged in SALTY publications where they played a direct advisory role, with some publications specifically discussing the role that essential voice advisors played in analysis and knowledge production [ 31 , 43 ] Advisors were co-leads in knowledge translation activities, including academic workshops [ 45 , 46 ] and other project related presentations as the project wrapped up.…”
Section: Designing Ltrc Research To Engage and Ensure Essential Voice...mentioning
confidence: 99%
“…Long-term care staff, who speak of a lack of adequate time as a structural barrier to providing relational care ( Barken & Lowndes, 2018 ), also express appreciation for volunteers’ capacity to support residents’ social needs ( Hunter et al, 2018 ; Söderhamn et al, 2012 ). Most studies focus on relationships volunteers maintain with long-term care residents, giving less attention to relationships with family caregivers and staff, despite the multi-directional benefits of involving volunteers in the care of long-term care residents with advanced dementia (e.g., Hande et al., 2021 ).…”
mentioning
confidence: 99%
“…In the few studies that do describe these relationships, volunteers have been described as having an “in-between” role where they are not quite a friend of the resident, and not quite a staff member either ( Weeks et al, 2008 ). This less defined, in-between role seems to allow volunteers to act as an intermediary between family members and staff when needed by either party, promoting more effective communication and continuity of care ( Hande et al, 2021 ). Current research also suggests that there are reciprocal benefits in the relationships between volunteers and family caregivers.…”
mentioning
confidence: 99%
See 1 more Smart Citation